Assessment of Chinese suitable habitats of Amomum tsao-ko in different climatic conditions - Guo, Tian-yu; Yang, Qing; Chen, Da-ju; Wang, Xiao-yu; Cheng, Qi-Qing; Wang, Shi; Hu, Ming-li (Frontiers in Plant Science, 2025)
IntroductionAmomum tsao-ko Crevost et Lemaire is not only a traditional Chinese medicine but also a significant cash crop in the border regions of southwest China. However, challenges pertaining to its growing environment, yield, and overall quality have considerably impeded its development. This paper investigates the responses of A. tsao-ko to climatic challenges, aiming to contribute to the long-term stability and sustainability of the industry.MethodsThe MaxEnt model, combined with ArcGIS software, was utilized to analyze key environmental factors and predict potential suitable habitats for A. tsao-ko under various climatic conditions. Furthermore, the volatile oils in A. tsao-ko samples from high-suitable habitats were analyzed using gas chromatography-mass spectrometry (GC-MS).ResultsThe results indicated that Bio04 (Temperature seasonality (standard deviation * 100)), Bio17 (Driest quarterly precipitation), and Bio12 (Precipitation of the wettest month) were the primary environmental factors influencing the distribution of A. tsao-ko. Under future climatic scenarios, it is expected to gradually adapt to new environmental conditions, with suitable habitats progressively shifting northward. The volatile oil extraction and GC-MS analysis revealed that the sample from Xishuangbanna (S8) exhibited not only the highest extraction rate (32.6 μL/g) but also the highest relative content of terpenes, particularly eucalyptol (29.26%).DiscussionS8 is regarded as a source of high-quality production that fulfills the criteria outlined in the Chinese Pharmacopoeia. The results show that Xishuangbanna can be used as a high-quality production area for A. tsao-ko planting, and large-scale artificial planting can be carried out to realize the sustainable development of A. tsao-ko industry and ecology.